(untitled) (Economics and region, 2024)
The article analyses the factors that determine the development of the passenger air transport market. It analyses the dynamics of international tourist arrivals in the regions of the world in 2019-2023 and identifies the busiest routes in the world in 2023. Also, it provides an analysis of the actual and forecast level of global traffic losses and the pace of its recovery. It was determined that according to the optimistic forecast, passenger traffic in 2027 should exceed the level of 2019 by 31%. It was also identified that the impact of global and local events has had a negative impact on both the tourism sector and the aviation industry. The surge in demand for air travel in Europe in 2023 caused flight delays by 400% during peak periods. The article examines the dynamics of the number of passengers who used the services of domestic airlines in Ukraine in 2011-2022. The paper outlines the most significant factors influencing the volume of passenger traffic, based on the actual state of the industry and current trends. It defines that the use of digital technologies will have advantages for both tourists and airlines.